2013
DOI: 10.1155/2013/768104
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Spindle Grinding of Si and Granite with a New Abrasive Disk

Abstract: An investigation was reported of a new attempt in the fabrication of an ultrafine abrasive tool for vertical spindle grinding. The principle of sol-gel was applied to granulate ultra-fine abrasives in order to reduce their aggregation. The granulated abrasives were then added to resin bonds, thereby forming ultra-fine abrasive grinding disks. Before grinding, the disks were dressed to expected flatness using a brazed diamond pad. The dressed grinding disks were then used to grind silicon wafers and natural gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The researchers controlled the full construction and production planning process with the help of different digital software applications, then they analysed the efficiency of the cutting disc. Yu et al 15 investigated a new method in the production of an ultrafine abrasive tool developed for vertical spindle grinding. The results of the research have shown that brazed diamond abrasives could dress the grinding discs with high efficiency and with satisfactory flatness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers controlled the full construction and production planning process with the help of different digital software applications, then they analysed the efficiency of the cutting disc. Yu et al 15 investigated a new method in the production of an ultrafine abrasive tool developed for vertical spindle grinding. The results of the research have shown that brazed diamond abrasives could dress the grinding discs with high efficiency and with satisfactory flatness.…”
Section: Literature Reviewmentioning
confidence: 99%